Measurement of dispersion of low-frequency ion oscillations in hybrid plasma waveguides - Antipov, V.S.; Antonov, A.N.; Balakirev, V.A.; Kovpik, O.F.; Kornilov, E.A.; Matyash, K.V.; Svichensky, V.G. (Вопросы атомной науки и техники, 2005)
A new technique of determining dispersion characteristics of the ion oscillations, excited in the hybrid plasma waveguide is elaborated (this device is a slow-wave structure, the passage channel of which is filled with plasma). This method is based on measuring changes in the shape of a single probing pulse propagating in the system. The method is tested in the process of determining the dispersion of low-frequency ion waves under the condition of the excitation of high-frequency powerful electron oscillations by an electron beam in the waveguide. The experimental data are compared with the analytical calculations. Розроблена методика визначення дисперсійних характеристик хвиль, порушуваних в гібридному плазмовому хвилеводі (уповільнююча структура, пролітний канал якої заповнений плазмою), заснована на вимірюванні зміни форми одиночного зондуючого імпульсу, що розповсюджується в системі. Випробування методу проведено при визначенні дисперсії низькочастотних іонних хвиль в умовах збудження в хвилеводі електронним пучком високочастотних електронних коливань великого рівня потужності. Проведено порівняння результатів експерименту з теоретичними розрахунками. Разработана методика определения дисперсионных характеристик волн, возбуждаемых в гибридном плазменном волноводе (замедляющая структура, пролётный канал которой заполнен плазмой), основанная на измерении изменения формы распространяющегося в системе одиночного зондирующего импульса. Испытание метода проведено при определении дисперсии низкочастотных ионных волн в условиях возбуждения в волноводе электронным пучком высокочастотных электронных колебаний большого уровня мощности. Проведено сравнение результатов эксперимента с теоретическими расчетами.